Determining Sustainable Rice Farming through Supply Chain Risk Management: A Case Study in Central Java, Indonesia - Agung Prabowo; Budi Pratikno; Jumadil Saputra; Sukono Sukono (International Journal of Supply Chain Management, 2019)
The government through the Department of Agriculture has been cooperating with Indonesian Insurance Services or PT. A suransiJasa Indonesia (PT. Jasindo), to implement an insurance program for farmers throughout the country known as rice farming insurance (RFI).The supply chain efficiency and risk management may be two causal factors to uplift the economic conditions of the agricultural communities. The premium rate for 1 hectare of land designated at 3% of the maximum benefit value of IDR 6,000,000. Consequently, the premium received by PT. Jasindo for each hectare is IDR 180,000 of which the Government subsidy pays IDR 144,000,andfarmers will pay the remaining IDR 36,000 of the premium. This research will determine the actuarially fair premium rate, both theoretically and using the data of rice harvest yield in Central Java Province from 1990-2017. The calculation, employing the rice harvest yield data, results in the premium rate. The farmers must pay for each hectare from IDR 56,000 (minimum) to IDR 161,600 (maximum) with an average value of IDR 110,750.Meanwhile,the standard deviation principle used, the premium results between IDR 78,151 and IDR 143,349. The rate of IDR 208,458 per hectare has theoretically generated if there are 100 participants per regency (city) or in size of 3,500 hectares throughout Central Java Province and IDR 182,846 per hectare if there are 10,000 participants or about 350,000 hectares. These values are not much different from RFI premium currently applied to farmers throughout Indonesia.